Hur bör handel med kryptovalutor beskattas - En rättsdogmatisk utredning om beskattning av kryptovalutor - Wiberg,Erik (2025)
This study aims to conduct a legal dogmatic analysis of how cryptocurrencies should be taxed under the Swedish income Tax Act. The thesis examines how this new type of currency should be classified under current law and which income category is most applicable for taxation. The study is based on legislation, preparatory works, case law from the Swedish Supreme Administrative Court (Högsta förvaltningsdomstolen), guidance from the Swedish Tax Agency (Skatteverket) and the doctrine. Cryptocurrencies are not defined as equity-based securities or debt instruments under the provisions of the Income Tax Act. They lack a connection to a legal entity and do not meet the requirements for either shareholders rights or state recognition as currency. As such, cryptocurrencies are classified as “other assets” under chapter 52 of the Income Tax Act. This entails that capital gains are fully taxable, while capital losses are only deductible at 70 percent. For natural persons, this means that trading in cryptocurrencies is generally taxed under the income category of capital. However, in cases where activity is carried out professionally, independently, and with continuity such as organized mining, taxation may fall under the income category of business income. For legal entities, all taxation occurs within the business income category, although capital gains provisions are used to calculate the results of cryptocurrency transactions. In determining the appropriate tax treatment, fundamental tax law principles such as the principle of legality, the principle of neutrality, and the principle of equal treatment are applied. The thesis demonstrates that current legal practise is based on a restrictive interpretation, treating cryptocurrencies as speculative assets rather than as currency. Although some countries have recognized crypto currencies as a legal tender, this may not yet influence the classification under Swedish law. The conclusion of this bachelor ́s thesis is that trading in cryptocurrencies should continue to be taxed in the income category of capital, under the rules for “other assets”, unless the legal requirements for business income are clearly met. The study also emphasizes the need for future legislative reform in step with the ongoing development of the cryptocurrency market.
Keywords: Bitcoin; Kryptovalutor; Fiatvalutor; Beskattning; Inkomstskattelagen; Crypto Currencies; Fiat Money; Taxation; Income Tax Act